4.3k views
3 votes
Which are the solutions of the quadratic equation x^2=-5x-3

User Trevorj
by
6.3k points

2 Answers

7 votes

Answer:

B

x₁ =
(-5-√(13) )/(2) , x₂=
(-5 + √(13) )/(2)

Explanation:

User Tomer Shiri
by
5.8k points
3 votes
The correct answer would be
(-5 +/- √(13) )/(2)

In order to solve for this you must first get the equation equal to 0.

x^2=-5x-3 ----> add 5x to both sides.
x^2 + 5x = -3 ----> add 3 to both sides.
x^2 + 5x + 3 = 0

Now knowing this we can use the coefficients of each one in descending order of power as a, b and c.

a = 1 (because it is the coefficient to x^2)
b = 5 (because it is the coefficient to x)
c = 3 (because it is the end number)

Now we can plug these values into the quadratic equation.


\frac{-b +/- \sqrt{b^(2) - 4ac } }{2a}


\frac{-5 +/- \sqrt{5^(2) - 4(3)(1) } }{2(1)}


(-5 +/- √(13) )/(2)

And those would be your two answers.
User IamMobile
by
6.4k points